Stereoselective Rh- and Cu-catalysed additions to imines and aldehydes - Smith, Joshua J. (2017)
Chapter 1.Copper-Catalysed Borylative Coupling of Vinylazaarenes and N-Boc Imines. Methodology for the copper-catalysed three-component couplings of vinylazaarenes, bis(pinacolato)diboron, and N-Boc imines has been developed. Oxidation of the initially formed boron species gives azaarene-containing, Boc-protected amino alcohols with reasonable to good diastereoselectivities. Additionally the synthetic utility of the reaction products have been demonstrated. The crude boron species have been shown to undergo a Suzuki-Miyaura cross coupling to give further functionalised products. Finally, facile deprotection of the reaction products is possible.